Zur Diffusion (kommunikations-)semantischer Modellgedanken aus dem Umkreis der deutschen Phänomenologie - Clemens Knobloch (Histoire Épistémologie Langage, 2021)
Starting from the history of semantic theory around 1900, this paper follows the traces left in semantics by the anti-psychologist networks of phenomenology, by the pupils of Franz Brentano, and by the Semasiology of Heinrich Gomperz. The central suggestion of the text is that Ogden & Richards’ The Meaning of Meaning (1923) paved the way toward transforming 19th century psychological semantics into modern referential semantics, still dominating linguistic thinking today. Alternative semantic theories based on “noetic” models of the thing-meant have remained marginal up to now, but have been more consequential in Ethnolinguistics and Ethnomethodology.